2006
DOI: 10.1542/peds.2005-0323
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Children and Adolescents: Impact of HIV Infection and Antiretroviral Treatment

Abstract: Generally parents of HIV-infected children 6 months to 4 years and 5 to 11 years of age generally reported lower mean QoL scores than did parents of uninfected children, although worse psychological functioning was reported for uninfected children. HIV-infected adolescents not receiving antiretroviral treatment had worse health perceptions and symptoms. We found no consistent QoL differences among children receiving different antiretroviral regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 18 publications
5
68
1
1
Order By: Relevance
“…14 The baseline QOL, before ART, of these children has been previously reported showing relatively low QOL scores compared to previous reports from untreated HIV-infected children in Western countries, and also lower than ART-treated Thai HIV-infected children from Northern Thailand. 3,13,15 Higher CD4% and CD4 cell count were associated with higher QOL scores in the health perception domain in Thai and Cambodian HIV-infected children. 13 Here, we report the effect of ART initiation on QOL in children over 144 weeks in the PREDICT study.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…14 The baseline QOL, before ART, of these children has been previously reported showing relatively low QOL scores compared to previous reports from untreated HIV-infected children in Western countries, and also lower than ART-treated Thai HIV-infected children from Northern Thailand. 3,13,15 Higher CD4% and CD4 cell count were associated with higher QOL scores in the health perception domain in Thai and Cambodian HIV-infected children. 13 Here, we report the effect of ART initiation on QOL in children over 144 weeks in the PREDICT study.…”
Section: Introductionmentioning
confidence: 92%
“…7 Unlike many other chronic illnesses, children with HIV infection are more likely to experience more difficulties in their daily lives (e.g., parental death from AIDS and social stigmatization 8,9 ) which may worsen their QOL. Lee et al 3 reported significantly lower QOL scores in HIV-infected children as compared to HIV-exposed but uninfected children. In addition, long-term requirement for life-saving antiretroviral therapy (ART) with pill burden and its side effects may affect children's QOL.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The questionnaire is based on a multidimensional conceptualization of health perceptions, physical resilience, physical functioning, psychological, social/role functioning, health care utilization and HIV-symptoms. This questionnaire was used in studies with HIV/AIDS infected children and has presented evidence of validity in this population 4,5,6 .…”
Section: Introductionmentioning
confidence: 99%